Preparation of ethogram for laying hens reared in cages - Ferreira, Joyce Augusta; Valentim, Jean Kaique; Machado, Luiz Carlos; Oliveira, Helder Freitas de (Revista de Ciências Agroveterinárias, 2022)
Poultry farming in Brazil has evolved significantly in the last decades, being still prominent, and contributing significantly to Brazilian agribusiness. One of the important factors for the success of poultry production is the efficient monitoring and control of the breeding environment, in addition to contributing to the promotion of a higher level of welfare for birds in confinement. However, the study of animal behavior is traditionally carried out through visual observations of animals, which consumes time and generates subjective decisions that are susceptible to human error. The general objective of this project is to elaborate an ethogram and to efficiently evaluate the behavior of laying hens housed in cages, through digital recordings. Birds of the commercial line Hisex Brown and Hisex White, 51 weeks old, reared in cages with capacity for two birds were used. An ethogram composed of 12 common events in this type of system was proposed to analysis the images. This ethogram recorded the following behaviors: “sitting”, “eating”, “drinking”, “exploring feathers”, “non-aggressive pecking”, “aggressive pecking”, “comfort movements”, “stopping”, “posture”, “stereotype”, “Open beak” and “open wings”. From the evaluation of this ethogram, it was noticed that the “eating” behavior occupied most of the birds' time (58% of the time), being followed by the “stop” behavior (17.3%) and “comfort movements” (8.8%). In the ambience and temperature conditions that the experiment was carried out, the chickens showed “open beak” behavior 100% of the time in the afternoon, indicating a clear situation of heat stress. In this way, the ethogram functioned as an indirect measurement of the degree of ambiance of these animals, which directly reflects in the care for animal welfare, a fundamental requirement for modern egg production.